2022
DOI: 10.1186/s12937-022-00777-x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of vitamin D supplementation for irritable bowel syndrome: a systematic review with meta-analysis

Abstract: Background Irritable bowel syndrome (IBS) is a chronic gastrointestinal disorder involving gut-brain interactions with limited effective treatment options. Vitamin D deficiency is commonly observed in patients with IBS, but whether vitamin D supplementation ameliorates IBS is controversial in randomized controlled trials. The present systematic review and meta-analysis explored the efficacy of vitamin D supplementation in patients with IBS. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 66 publications
1
12
1
Order By: Relevance
“…We clarified the methodological flaws of Chong et al [55] in our recently published editorial [59]. In another recent review by Haung et al [60], vitamin D was effective in improving IBS-SSS which is also contradictory to our findings. This difference is attributed to the narrow and defective searching technique excluding three includable studies [29,31,32] especially Williams et al [31] and Jalili et al, 2019 [29] which showed no effect of vitamin D on IBS-SSS.…”
Section: Discussioncontrasting
confidence: 45%
“…We clarified the methodological flaws of Chong et al [55] in our recently published editorial [59]. In another recent review by Haung et al [60], vitamin D was effective in improving IBS-SSS which is also contradictory to our findings. This difference is attributed to the narrow and defective searching technique excluding three includable studies [29,31,32] especially Williams et al [31] and Jalili et al, 2019 [29] which showed no effect of vitamin D on IBS-SSS.…”
Section: Discussioncontrasting
confidence: 45%
“…Jalili et al conducted a randomized, double-blind, placebo-controlled clinical trial to assess the impact of Vit-D supplementation on symptoms severity and quality of life (QOL) in IBS patients and found that compared to the placebo group, Vit-D therapy could markedly improve the symptoms and QOL of IBS patients [9]. Similarly, a systematic review and meta-analysis including 4 randomized, placebo-controlled trials showed that Vit-D supplementation was remarkably superior to placebo in improving the symptom severity (WMD: -84.21, 95% CI: -111.38 to -57.05, I 2 = 73.2%; WMD: -28.29, 95% CI: -49.95 to -6.62, I 2 = 46.6%, respectively) and QOL (WMD: 14.98, 95% CI: 12.06 to 17.90, I 2 = 0.0%; WMD: 6.55, 95% CI: -2.23 to 15.33, I 2 = 82.7%, respectively) of IBS patients [25]. However, the other randomized, double-blind, placebocontrolled study by Williams et al demonstrated that there were no improvements in the IBS symptom severity and QOL between the trial (Vit-D supplementation) and placebo groups [10].…”
Section: Discussionmentioning
confidence: 94%
“…Jalili et al conducted a randomized, double-blind, placebo-controlled clinical trial to assess the impact of Vit-D supplementation on symptoms severity and quality of life (QOL) in IBS patients and found that, compared to the placebo group, Vit-D therapy could markedly improve the symptoms and QOL of IBS patients [ 14 ]. Similarly, a systematic review and meta-analysis including four randomized, placebo-controlled trials showed that Vit-D supplementation was remarkably superior to placebo in improving the symptom severity (WMD: −84.21, 95% CI: −111.38 to −57.05, I 2 = 73.2%; WMD: −28.29, 95% CI: −49.95 to −6.62, I 2 = 46.6%, respectively) and QOL (WMD: 14.98, 95% CI: 12.06 to 17.90, I 2 = 0.0%; WMD: 6.55, 95% CI: −2.23 to 15.33, I 2 = 82.7%, respectively) of IBS patients [ 30 ]. However, the other randomized, double-blind, placebo-controlled study by Williams et al demonstrated that there were no improvements in the IBS symptom severity and QOL between the trial (Vit-D supplementation) and placebo groups [ 15 ].…”
Section: Discussionmentioning
confidence: 99%